2010
DOI: 10.1093/treephys/tpq025
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of gas exchange and water relations in deciduous and evergreen trees in monsoonal dry forests of Thailand

Abstract: This study compared leaf gas exchange, leaf hydraulic conductance, twig hydraulic conductivity and leaf osmotic potential at full turgor between two drought-deciduous trees, Vitex peduncularis Wall. and Xylia xylocarpa (Roxb.) W. Theob., and two evergreen trees, Hopea ferrea Lanessan and Syzygium cumini (L.) Skeels, at the uppermost canopies in tropical dry forests in Thailand. The aims were to examine (i) whether leaf and twig hydraulic properties differ in relation to leaf phenology and (ii) whether xylem ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 56 publications
1
30
0
6
Order By: Relevance
“…Além disso, diferenças pronunciadas na g s entre espécies decíduas e sempre verdes são comumente descritas em diversos ecossistemas sazonalmente secos (Chen et al 2009;Mediavilla & Escudero, 2003;Ishida et al 2006) e são interpretadas com uma demanda conflitante entre LF e eficiência hidráulica (Sobrado 1993;Ishida et al 2010;Fu et al 2012). Embora não observamos diferenças significativas na g s entre espécies decíduas e sempre verdes, acreditamos que a b a maior taxa fotossintética por unidade de massa nas espécies decíduas, ocorreu possivelmente por que essas espécies exibiram menor massa foliar por unidade de área, o que representa uma barreira física a difusão do CO 2 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Além disso, diferenças pronunciadas na g s entre espécies decíduas e sempre verdes são comumente descritas em diversos ecossistemas sazonalmente secos (Chen et al 2009;Mediavilla & Escudero, 2003;Ishida et al 2006) e são interpretadas com uma demanda conflitante entre LF e eficiência hidráulica (Sobrado 1993;Ishida et al 2010;Fu et al 2012). Embora não observamos diferenças significativas na g s entre espécies decíduas e sempre verdes, acreditamos que a b a maior taxa fotossintética por unidade de massa nas espécies decíduas, ocorreu possivelmente por que essas espécies exibiram menor massa foliar por unidade de área, o que representa uma barreira física a difusão do CO 2 .…”
Section: Discussionunclassified
“…Embora espécies decíduas e sempre verdes demonstrem diferenças entre o uso de água e nutrientes (Kikuzawa 1991;Givnish 2002;Ishida et al 2010), ainda não é claro se durante o período de maior disponibilidade hídrica essas diferenças são mantidas. Em relação às trocas gasosas e uso da água, espécies decíduas são menos conservativas no uso da água, transpiram a elevadas taxas no período chuvoso em troca de maior ganho de carbono (Mediavilla & Escudero, 2003).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…All measurements were conducted in November to December 2009, which is the beginning of the dry season. In the early dry season, leaf photosynthetic activities seemed high, especially in the dry evergreen forest, with high water storage in a thick soil layer 27,61,62 . In fact, the stomatal conductance in several trees showed relatively higher value in the early dry season 10 and soil and regolith were widely distributed throughout the study site 51 to a thickness exceeding 10 m.…”
mentioning
confidence: 99%
“…Detailed studies comparing plant water relations and hydraulics of evergreen and drought deciduous trees have been carried out in dry rainforests in Queensland [5] and dry forests in Costa Rica [6]. More recently, there have been studies comparing and contrasting the ecophysiology of evergreen trees from semi-evergreen forests and deciduous trees from dry forests in Thailand [7][8][9]. These latter studies have shown differences in ecophysiological adaptations of evergreen compared to drought deciduous trees in Thai forests.…”
Section: Introductionmentioning
confidence: 99%